The constitutional guarantee of the provision of local Social Services in Spain: a comparative regional study - Forns i Fernández, Maria Victòria; Alegre-Agís, Elisa (Revista de Investigações Constitucionais, 2024)
This article outlines the public architecture of social services in Spain from the perspective of the constitutional guarantee of the provision of local social services. For this, the Spanish Constitution is analyzed, as well as the 17 laws of social services corresponding to the different Autonomous Communities. It is therefore a comparative regional study in which the local authority is the essential unit to deploy social services, responding to the principles of universality, proximity, and decentralization; mandated by Spanish legislation. These and other complementary laws establish universal access to social services for all citizens, determine the territorial structure, the competences of the different administrations, rights holders, typologies of services and benefits and their articulation to ensure the quality of life and social welfare of all citizens.